Figurations on Subjectivity, Government and the State in Eighteenth and Nineteenth Century English Fiction and Political Philosophy - Dávilo, Beatriz (Foro Interno, 2019)
This article examines figurations of the relationship between subjectivity, government and State during the consolidation of the link between liberalism and rising capitalism in the eighteenth and nineteenth century history of English political thought. From an archaeological perspective, the aim is to analyze the political and philosophical questions around the problem of liberal governmentality by means of a review of philosophical and literary texts. This analysis shows that a shift occurred from Providence to the State as the reference and constraint of individual and collective conduct. The development of a self-deciphering exercise accompanied a decline in confidence in calculating reason and acceptance of uncertainty regarding the results of one’s own actions.